Lifetime inequality and redistribution - Mike Brewer; Monica Costa Dias; Jonathan Shaw (Institute for Fiscal Studies (IFS), 2012)
In this paper we look at lifetime inequality to address two main questions: How well does a modern tax system, based on annual information, target lifetime inequality? What aspects of the tranfser system are most progressive from a lifetime perspective? To answer to these questions it is crucial to relate lifetime and annual inequality and determine the main building blocks of lifetime disparities. We look at lifetime inequality and the redistribution properties of taxes and benefits using a dynamic life-cycle model of women's education, labour supply and savings with family dynamics and rich individual heterogeneity in preferences and productivity. The model is coupled with a detailed description of the UK personal tax and benefit system and is estimated on UK longitudinal data covering the 1990s and early 2000s. We show that the tax and benefits system is more redistributive from an annual than from a lifetime perspective, and it most progressive at the bottom of the income distribution in both cases. We then establish that heterogeneity in family experiences throughout adult life is the main vehicle through which the tax and benefits system moderates lifetime inequality. Although transitory, family conditions under which working is especially costly, such as lone-motherhood, are escpecially prevalent among the lifetime poor. By targeting this group, particularly using policies specifically designed to improve the work incentives of those with the lowest earnings capacity, the tax and benefits system does achieve life-cycle redistribution. Other policies like universal benefits towards family with children are less well targeted towards the lifetime poor but are more progressive and improve the work incentives in the middle 60% of the distribution of lifetime income.
Keywords: H23; H24; I24; I38; J22; J24; 330; female laboursupply; life-cycle; inequality; redistribution; taxes